Exploring Lorentz-violating effects of Kalb-Ramond field on charged black hole thermodynamics and photon dynamics - Sucu, Erdem; Sakalli, Izzet (Amer Physical Soc, 2025)
This study explores the influence of the Kalb-Ramond (KR) field, characterized by Lorentz-violating effects, on the structure, thermodynamics, and observational phenomena of Reissner-Nordstr & ouml;m-like black holes. By introducing a modified Einstein-Hilbert action incorporating the KR field's nonminimal coupling with the & imacr;Ricci tensor, we derive a spherically symmetric black hole solution. The Lorentzviolating parameter L alters the black hole's horizon structure, curvature invariants, and thermodynamic properties, such as Hawking temperature and entropy, with exponential quantum corrections offering deeper insights into high-energy phenomena. Photon dynamics in both vacuum and plasma environments reveal refractive effects due to the KR field, with weak gravitational lensing analyzed using the GaussBonnet theorem and perturbative methods, including higher-order deflection corrections. Observational signatures like modified photon spheres, lensing angles, and shadows are discussed, providing potential avenues for experimental validation.
Keywords: Hawking Radiation; Entropy